2021
DOI: 10.3892/etm.2021.10469
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation increases neurological function and endogenous neural stem cell migration via the SDF‑1α/CXCR4 axis after cerebral infarction in rats

Abstract: Neural stem cell (NSC) migration is closely associated with brain development and is reportedly involved during recovery from ischaemic stroke. Chemokine signalling mediated by stromal cell-derived factor 1α (SDF-1α) and its receptor CXC chemokine receptor 4 (CXCR4) has been previously documented to guide the migration of NSCs. Although repetitive transcranial magnetic stimulation (rTMS) can increase neurological function in a rat stroke model, its effects on the migration of NSCs and associated underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Furthermore, cognitive functional recovery could arise from the elevated levels of SDF-1α and CXCR4 in ischemia rats [70]. Additionally, our prior study has shown that 10 Hz rTMS could signi cantly increase the protein expression levels of SDF-1α and CXCR4 in striatum in MCAO rats,which contributed to the restoration of motor function [23]. Evidence is accumulating that SDF-1α is involved in axonal path nding, outgrowth, and branching, while axonal sprouting occurs from the intact cortex into the peri-injured cortex and striatum [71].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, cognitive functional recovery could arise from the elevated levels of SDF-1α and CXCR4 in ischemia rats [70]. Additionally, our prior study has shown that 10 Hz rTMS could signi cantly increase the protein expression levels of SDF-1α and CXCR4 in striatum in MCAO rats,which contributed to the restoration of motor function [23]. Evidence is accumulating that SDF-1α is involved in axonal path nding, outgrowth, and branching, while axonal sprouting occurs from the intact cortex into the peri-injured cortex and striatum [71].…”
Section: Discussionmentioning
confidence: 97%
“…Rats in the RA and MA groups received an AMD3100(medium saline; 2 mg/kg; i.p.) injection every other day since 2 days after MCAO until euthanasia according to previous reports [23].…”
Section: Administration Of Amd3100mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, SDF-1α facilitates the attraction of neural stem/progenitor cells (NSCs) towards the site of brain injury by engaging with its receptor, chemokine receptor type 4 (CXCR4). CXCR4 is predominantly found on neural stem/progenitor cells, and cells that express CXCR4 migrate in response to the concentration gradient of SDF-1α [ 151 , 152 ]. NSCs are responsible for neurogenesis and brain plasticity that could replace dead neurons [ 153 ].…”
Section: Exerkines and CImentioning
confidence: 99%